(untitled) (Bangladesh Journal of Physiology and Pharmacology, 2014)
Bangladesh is overburdened with cervical cancer. In each year 13,000 new cases enter in this series. Visual inspection of cervix with acetic acid (VIA) is adopted as national cervical cancer (ca cx) screening program, in Bangladesh. Positive VIA, abnormal cytology, positive HPV or suspicious looking cervices are referred for secondary screening (Colposcopy). Chittagong Medical College Hospital (CMCH) acts as a primary screening and secondary referral center. With the aim to identify the weakness of present ca cx screening system one year (April 2013 to March 2014) records were evaluated. A total 1853 VIA & 714 colposcopy cases were analyzed from records of CMCH, Bangladesh. The age of population range from 16 -71 years and most were between 30-49 years. In primary screening VIA +ve cases were 6% (n=120). After secondary screening 43.69% (n=312) were identified as abnormal; among those precancerous lesion (CIN) 37.82% (n= 270); ca cx 1.54% (n=11); suspicious 4.34% (n=31). Histopathology proven CIN 12.04% (n=86) & ca cx 2.10% (n=15). Cases received treatment (LEEP) were only 09.38% (n=67). Finally among total population, 56.30% (n=402) were declared normal, 14.15% (n=101) had definite pathology and 29.55% (n=211) remained undetermined (as they failed to re-produce their histology report at the final step of secondary screening). This study found a bottleneck caused by present service delivery systems; lack of prompt referring and re-reporting to primary center within a schedule time (after receiving management) and lack of recall system both from primary and secondary screening center. To make the program successful have to have schedule for re-reporting and recalling. DOI: http://dx.doi.org/10.3329/bjpp.v30i1.20790 Bangladesh J Physiol Pharmacol 2014; 30(1):25-28